计算:(m+3m+5m+…+2011m)-(2m+4m+6m+…+2010m)=
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 19:21:41
计算:(m+3m+5m+…+2011m)-(2m+4m+6m+…+2010m)=计算:(m+3m+5m+…+2011m)-(2m+4m+6m+…+2010m)=计算:(m+3m+5m+…+2011m)
计算:(m+3m+5m+…+2011m)-(2m+4m+6m+…+2010m)=
计算:(m+3m+5m+…+2011m)-(2m+4m+6m+…+2010m)=
计算:(m+3m+5m+…+2011m)-(2m+4m+6m+…+2010m)=
2010m/2=1005m
(m+3m+5m+…+2011m)-(2m+4m+6m+…+2010m)
=(m+3m+5m+…+2011m)-2m-4m-6m-...-2010m
=m-2m+3m-4m+5m-6m+...+2009m-2010m+2011m
=-m-m-m+...-m+2011m
=-1005m+2011m
=1006m
1006m
解答此题关键是拆项与组合:原式=m+(3m-2m)+(5m-4m)+(7m-6m)+...+(2011m-2010m),后面的偶数项一共有1005项,所以原式=m+1005m=1006m。
计算:(m+3m+5m+…+2011m)-(2m+4m+6m+…+2010m)=
计算(m+3m+5m+.+2011m)减(2m+4m+6m+.+2012m)=
计算(m+3m+5m+...+2011m)-(2m+4m+6m+...+2010m)=
计算(m+3m+5m……+2009m)—(2m+4m+6m+2008m)=
计算:(m+3m+5m+…+2015m)-(2m+4m+6m+…+2014m)=
计算:(m+3m+5m+...+2009m)-(2m+4m+6m+...+2008m)
计算:(m+3m+5m+...+2009m)-(2m+4m+6m+...+2010m)
计算(m+3m+5m+7m+.+2009m)-(2m+4m+6m+.+2008m)
计算(m+3m+5m+7m+.+2013m)-(2m+4m+6m+.+2012m)
计算:m-2m-3m+4m-5m-6m+7m-8m-9m+...+2002m-2003m-2004m
计算(m+3m+5m+.+2009m)-(2m+4m+6m+.+2010m)=多少
计算(m+3m+5m+…+2013m)-(2m+4m+6m+…+2014m)=什么?A-1007m、B-1006m、C-1005m、D-1004m.
计算:(m+3m+5m+……2013m)-(2m+4m+6m+…2012m)=_
计算:(m+3m十5m+…+2009m)一(2m十4m十6m十…2008m)=
计算:(m+3m+5m+…+2009m)-(2m+4m+6m+…+2008m)=_______
合并同类项m-2m+3m-4m+5m-.+2011m-2012m
m+3m+5m+...+2011m-2m-4m-...-2010m等于多少?
(m+3m+5m+7m+.+2011m)-(2m+4m+6m+.+2010m) 要说理由!